2010
DOI: 10.21608/eajbsa.2010.15189
|View full text |Cite
|
Sign up to set email alerts
|

Cladistic analysis of Egyptian horse flies (Diptera: Tabanidae) based on morphological data

Abstract: The family Tabanidae is one of the important families of superfamily Tabanoidea, having medical and veterinary importance. In Egypt, there is no strict cladistic approach on tabanid flies phylogeny yet. The 20 available Egyptian tabanids under 2 subfamilies are analyzed cladistically. Cladistic analysis is based on 91 morphological characters depending on Single linkage, UPGMA, Complete linkage clustering methods (Cophenetic correlation value). This produces a well-resolved and firmly supported phylogenetic hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…They found no support for Mackerras' subfamilies in their study. El‐Hassan et al () used 91 morphological characters scored only from Egyptian exemplars and found that Atylotus Osten Sacken and Tabanus may be nonmonophyletic. Cywinska et al () collected Cytochrome Oxidase I sequences for many species of Canadian Tabanidae.…”
Section: Introductionmentioning
confidence: 99%
“…They found no support for Mackerras' subfamilies in their study. El‐Hassan et al () used 91 morphological characters scored only from Egyptian exemplars and found that Atylotus Osten Sacken and Tabanus may be nonmonophyletic. Cywinska et al () collected Cytochrome Oxidase I sequences for many species of Canadian Tabanidae.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the tabanid fauna of the Levant is only fragmentarily described, no valid checklists exist from Syria and Lebanon (Surcouf 1926), and in Iraq (Leclercq 1963), Israel (Theodor 1965), and Egypt (Abu El‐Hassan et al 2010) no solid surveys were performed for many decades. Even for the well‐researched Saudi Arabia, Leclercq (2000) recently emphasized that there is still a great need for further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Lebanon is known for its diverse flora (Danin 1988) and fauna (Kosswig 1955), but the knowledge about horse flies is only fragmentary (Leclercq 1960, 1966). In contrast, the fauna of Turkey (Kilic 2006), Saudi Arabia (Leclercq 2000) Jordan (Al‐Talafha et al 2004, 2005, Müller et al 2011b), Israel (Theodor 1965), and Egypt (Efflatoun 1930, Abu El‐Hassan et al 2010) is relatively well known.…”
Section: Introductionmentioning
confidence: 99%